1995
DOI: 10.1002/eji.1830250619
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania infantum‐specific T cell lines derived from asymptomatic dogs that lyse infected macrophages in a major histocompatibility complex‐restricted manner

Abstract: Protective immunity to leishmaniasis has been demonstrated in murine models to be mediated by T cells and the cytokines they produce. We have previously shown that resistance to experimental Leishmania infantum infection in the dog, a natural host and reservoir of the parasite, is associated with the proliferation of peripheral blood mononuclear cells (PBMC) to parasite antigen and to the production of interleukin-2 and tumour necrosis factor. In this study we show that PBMC from asymptomatic experimentally in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
90
2
17

Year Published

1999
1999
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(112 citation statements)
references
References 36 publications
3
90
2
17
Order By: Relevance
“…In this study, the clinical classification was chosen because of its widespread adoption in the literature of both the Old and New World, whether in natural or experimental infection (PINELLI et al, 1994(PINELLI et al, , 1995TRAVI et al, 2001;FERNÁNDEZ-PÉREZ et al, 2003;COSTA-VAL, 2004;REIS et al, 2006a, b). The analysis revealed dysproteinemia, azotemia and anemia as the main laboratory findings in dogs naturally infected with different clinical forms of visceral leishmaniasis.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the clinical classification was chosen because of its widespread adoption in the literature of both the Old and New World, whether in natural or experimental infection (PINELLI et al, 1994(PINELLI et al, , 1995TRAVI et al, 2001;FERNÁNDEZ-PÉREZ et al, 2003;COSTA-VAL, 2004;REIS et al, 2006a, b). The analysis revealed dysproteinemia, azotemia and anemia as the main laboratory findings in dogs naturally infected with different clinical forms of visceral leishmaniasis.…”
Section: Discussionmentioning
confidence: 99%
“…The high percentage of specific lysis of the L. infantum-infected J774 murine macrophage line suggests that an anti-Leishmania cytotoxic response is generated in protected mice. The lysis of parasitized macrophages has been observed in mice (62), hamsters (63), dogs (64), and humans (65) and might be an important mechanism involved in resistance to leishmaniasis. Although the characterization of the cells involved in the cytotoxic activity observed in the present study was not done, several reports have shown that both class I-restricted cytotoxic CD8 ϩ and CD4 ϩ T cells as well as NK cells are potential effector cells.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of dogs asymptomatic for VL has been associated with the activation of Th1 cells that produce interferon (IFN)-c, interleukin (IL)-2 and tumor necrosis factor (TNF)-a (Pinelli et al, 1994;Pinelli et al, 1995). Leishmania parasites are killed by macrophages activated by IFN-c producing lymphocytes via a nitric oxide dependent mechanism (Vouldoukis et al, 1996;Holzmuller et al, 2005).…”
Section: Introductionmentioning
confidence: 99%